2018
DOI: 10.1016/j.palaeo.2018.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Coral geochemical record of submarine groundwater discharge back to 1870 in the northern South China Sea

Abstract: The importance of submarine groundwater discharge (SGD) is becoming increasingly recognized because of its potential significance as a source of dissolved species. To explore the probable coral geochemical signal of SGD and verify the validity of potential reliable proxies, multiple geochemical proxies over the last 137 years were identified from a Porites coral near a subterranean estuary in the northern South China Sea, where the SGD was reported to be the predominant flux of terrestrial waters to the coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 92 publications
1
16
0
Order By: Relevance
“…Coral Ba/Ca ratios exhibited regular seasonal peaks in austral autumn, fluctuating from~4.1 to~7.0 μmol/mol, with background values also exhibiting a marginal increase (p < 0.01) (Figure 3d). Such seasonal peaks and variation range are comparable to the previous reported Ba/Ca patterns in most corals across the Caribbean and Indo-Pacific regions, which are commonly attributed to the seasonal delivery of Ba by river runoff (Fallon et al, 1999;Jupiter et al, 2008;Lewis et al, 2018;McCulloch et al, 2003;Sinclair & McCulloch, 2004;Prouty et al, 2010;Saha, Rodriguez-Ramirez, et al, 2018), upwelling (Alibert & Kinsley, 2008;Lea et al, 1989;Reuer et al, 2003;Shen et al, 1992;Shen & Sanford, 1990), or groundwater (Alibert et al, 2003;Jiang et al, 2018).…”
Section: Terrestrial Signal In Monthly Coral Geochemical Records 51supporting
confidence: 88%
See 1 more Smart Citation
“…Coral Ba/Ca ratios exhibited regular seasonal peaks in austral autumn, fluctuating from~4.1 to~7.0 μmol/mol, with background values also exhibiting a marginal increase (p < 0.01) (Figure 3d). Such seasonal peaks and variation range are comparable to the previous reported Ba/Ca patterns in most corals across the Caribbean and Indo-Pacific regions, which are commonly attributed to the seasonal delivery of Ba by river runoff (Fallon et al, 1999;Jupiter et al, 2008;Lewis et al, 2018;McCulloch et al, 2003;Sinclair & McCulloch, 2004;Prouty et al, 2010;Saha, Rodriguez-Ramirez, et al, 2018), upwelling (Alibert & Kinsley, 2008;Lea et al, 1989;Reuer et al, 2003;Shen et al, 1992;Shen & Sanford, 1990), or groundwater (Alibert et al, 2003;Jiang et al, 2018).…”
Section: Terrestrial Signal In Monthly Coral Geochemical Records 51supporting
confidence: 88%
“…As for coral Ba/Ca, the scenario is more complicated due to the complexity of biogeochemistry of Ba in coastal coral skeletons (Chen et al, 2011;Lewis et al, 2018;Saha, Webb, et al, 2018;Sinclair, 2005;Tanzil et al, 2019). Monthly variability of coral Ba/Ca is not only always corresponded to river discharge peaks during wet season but would also show seasonal cycles or anomalously episodic spikes possibly linked to upwelling (Alibert & Kinsley, 2008;Lea et al, 1989), submarine groundwater (Alibert et al, 2003;Jiang et al, 2018), biological activity (Gillikin et al, 2006;Lewis et al, 2018;Saha, Webb, et al, 2018;Sinclair, 2005;Wyndham et al, 2004), anomalously lower temperature (Chen et al, 2011), or sediment resuspension (Alibert et al, 2003;Esslemont et al, 2004). Similarly, coral δ 13 C also has limitations as an environmental proxy as drivers such as internal carbon source, coral-symbionts metabolism, kinetic effects, and other environmental variables may vary case by case (e.g., Allison & Finch, 2012;Deng et al, 2013;Grottoli, 2002;McConnaughey et al, 1997;McConnaughey, 2003;Swart, Healy, et al, 1996;Swart, Leder, et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…They found strong correlations between annual precipitation and the Ba/Ca coral time-series and concluded that Ba/Ca ratios can be used as a proxy of precipitation, which in the Yucatan is a direct indicator of SGD as there is minimal surface runoff (Young et al, 2008). Jiang et al (2018) measured variations of REE/Ba and REE/Ca ratios in coral samples from Hainan Island, China, and used these as a long-term (>100 year) proxy for SGD in the study area. They observed an increase in the reconstructed SGD corresponding to the escalating trend of local rainfall and suggested that "coral paleohydrological records can contribute to model-data comparisons in SGD models under different pumping scenarios."…”
Section: Looking To the Future By Studying The Pastmentioning
confidence: 99%
“…One of the most commonly studied invertebrates in this respect are corals. Sometimes the impact of SGD on corals causes no apparent physical stress, but it can affect the isotopic signature, such as by altering the δ 18 O and δ 15 N signatures or rare earth element ratios of corals on century to Holocene scales [101,108,110]. More often, the presence of SGD in a coral ecosystem results in a reduction of coral cover and coral species diversity [26,74,94].…”
Section: Animalsmentioning
confidence: 99%